Study protocol of the global Effisayil 1 Phase II, multicentre, randomised, double-blind, placebo-controlled trial of spesolimab in patients with generalized pustular psoriasis presenting with an acute flare - Choon, Siew Eng; Lebwohl, Mark G; Marrakchi, Slaheddine; Burden, A David; Tsai, Tsen-Fang; Morita, Akimichi; Navarini, Alexander A; Zheng, Min; Xu, Jinhua; Turki, Hamida; Rajeswari, Sushmita; Deng, Hongjie; et al. (BMJ open, 2021)
IntroductionGeneralized pustular psoriasis (GPP) is a rare, potentially life-threatening disease characterised by recurrent flares of widespread neutrophilic aseptic skin pustular eruption. Despite the availability of approved biologics for GPP in Japan, Taiwan and Thailand, associated evidence is largely based on uncontrolled studies in which acute flares were not directly assessed. Therefore, there is a high unmet need to investigate new rapid-acting effective treatments that resolve symptoms associated with acute GPP flares. A prior Phase I proof-of-concept study showed rapid improvements in skin and pustule clearance with a single intravenous dose of spesolimab, a novel anti-interleukin-36 receptor antibody, in patients presenting with an acute GPP flare. Here, we present the design and rationale of Effisayil 1, a global, Phase II, placebo-controlled study to evaluate the efficacy, safety and tolerability of spesolimab in patients presenting with an acute GPP flare.Methods and analysisAt least 51 patients with an acute GPP flare will be randomised 2:1 to receive a single 900 mg intravenous dose of spesolimab or placebo and followed for up to 28 weeks. The primary endpoint is a Generalized Pustular Psoriasis Physician Global Assessment (GPPGA) pustulation subscore of 0 (pustule clearance) at Week 1. The key secondary endpoint is a GPPGA score of 0 or 1 (clear or almost clear) at Week 1. Safety will be assessed over the study duration by the occurrence of treatment-emergent adverse events. Blood and skin biopsies will be collected to assess biomarkers. Superiority of spesolimab over placebo in the proportion of patients achieving the primary and key secondary endpoints will be evaluated.Ethics and disseminationThe study complies with the ethical principles of the Declaration of Helsinki, the International Council for Harmonisation’s Good Clinical Practice and local regulations. Ethics committee approvals have been obtained for each centre from all participating countries and are listed in online supplementary file 1. Primary results will be published in a peer-reviewed journal.Trial registration detailsClinicalTrials.gov identifier: NCT03782792; Pre-results.